Solid lipid nanoparticles modified with stearic acid–octaarginine for oral administration of insulin - Zhang ZH (Dove Medical Press, 2012)
Zhen-Hai Zhang,1,2 Yin-Long Zhang,2 Jian-Ping Zhou,2 Hui-Xia Lv21Jiangsu Province Academy of Traditional Chinese Medicine, Nanjing, China; 2Department of Pharmaceutics, China Pharmaceutical University, Nanjing, ChinaAbstract: The aim of this study was to design and characterize solid lipid nanoparticles (SLNs) modified with stearic acid–octaarginine (SA-R8) as carriers for oral administration of insulin (SA-R8-Ins-SLNs). The SLNs were prepared by spontaneous emulsion solvent diffusion methods. The mean particle size, zeta potential, drug loading, and encapsulation efficiency of the SA-R8-Ins-SLNs were 162 nm, 29.87 mV, 3.19%, and 76.54%, respectively. The zeta potential of the SLNs changed dramatically, from -32.13 mV to 29.87 mV, by binding the positively charged SA-R8. Morphological studies of SA-R8-Ins-SLNs using transmission electron microscopy showed that they were spherical. In vitro, a degradation experiment by enzymes showed that SLNs and SA-R8 could partially protect insulin from proteolysis. Compared to the insulin solution, the SA-R8-Ins-SLNs increased the Caco-2 cell's internalization by up to 18.44 times. In the in vivo studies, a significant hypoglycemic effect in diabetic rats over controls was obtained, with a SA-R8-Ins-SLN pharmacological availability value of 13.86 ± 0.79. These results demonstrate that SA-R8-modified SLNs promote the oral absorption of insulin.Keywords: solid lipid nanoparticles, cell penetration peptides, stearic acid octaarginine, insulin, oral administration